Empirical Analysis on Financial Performance through Cash Flow Statements - Sankar, D. Guna; Kumar, B. Ravi (International Journal of Accounting & Finance Review, 2018)
The present case study is an attempt to anlyze the financial performance of the company by using cash flow statements. The study findings can be helpful for the management of Zuari Cement Ltd., Dondapadu to improve their financial performance and formulate policies that will improve their performance.